IMPROVING THE TREATMENT OF PERIODONTAL DISEASES IN WORKERS EXPOSED TO STYRENE POLYMERS - Sidikov Khotamjon Muminjon ugli; Nazarova Nodira Sharipovna (PEDAGOGS, 2024)
Relevance: in the process of intensive industrial development, the study of the role of harmful and health-related factors of the production environment is timely and very important. After all, unfavorable working conditions contribute to the formation of various pathological processes in the human body (Amirov N.H., 2016). The long-term influence of a complex of production factors simultaneously with the deterioration of the health of workers, as a rule, can lead to pathological changes in the mucous membrane of the oral cavity, periodontal diseases, hard tissues of teeth (Galiullin A.N., 2014)